Quantitative Evaluation of Masticatory Performance with Two-Color Mixing Ability Test: Development of a New Digital Method - Yousof, Yaman; Salleh, Nosizana Mohd; Yusof, Farazila (Quintessence Publishing, 2020)
Purpose: To develop a new digital method for color-mixing analysis and to evaluate the validity of this method for quantifying masticatory performance. Materials and Methods: Specimens of red-green (RG) chewing gum were prepared as a bicolor test food. A total of 300 specimens were masticated by 20 healthy volunteers for different numbers of mastication cycles (from 1 to 25). The boluses were flattened and scanned, and the digital images were analyzed using ImageJ software. Two parameters (spatial and value) of color mixing were measured, and multiple regression analysis was performed to estimate the number of mastication cycles. The estimated number of mastication cycles that the healthy reference cohort needed to achieve a certain degree of color mixing was proposed as the mastication index (MI). The validity of this method was assessed using Pearson correlation between the MI and concurrent measurements with ViewGum software (variance of hue) within a group of 10 healthy subjects and 10 complete denture wearers. Results: Independent samples t test showed a significant difference in MI between healthy subjects and denture wearers (P <.001). A significant correlation was observed between the MI and ViewGum outcomes (r =-0.95, P <.001). Conclusion: The new proposed method proved to be valid and has the potential for evaluating masticatory performance in both research and clinical settings. ©2020 by Quintessence Publishing Co Inc.